The effect of benson relaxation therapy on sleep quality among perimenopausal women: A pre-experimental study - Ade Marlisa Rahmadayanti; Rini Anggeriani; Titin Apriyani; Windi Diawaroh (Lentera Perawat, 2026)
Background: Sleep disturbances are commonly experienced by perimenopausal women due to hormonal fluctuations and psychosocial changes. Non-pharmacological interventions are increasingly recommended to manage sleep problems safely and effectively in this population. Benson relaxation therapy is a mind–body intervention that induces a relaxation response and has shown potential benefits for sleep regulation. Objective: This study aimed to examine the effect of Benson relaxation therapy on sleep quality among perimenopausal women. Methods: This study employed a quantitative pre-experimental design using a one-group pre-test and post-test approach. The study was conducted at Tulung Selapan Primary Health Center, Ogan Komering Ilir Regency, Indonesia, in November 2024. Participants were selected using purposive sampling based on inclusion criteria, including perimenopausal women aged 45–55 years who experienced sleep disturbances and were not using sleep-affecting medications. Benson relaxation therapy was administered for five consecutive days with a duration of 10 minutes per session. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed using descriptive statistics and paired statistical tests. Results: The results demonstrated an improvement in sleep quality following Benson relaxation therapy. The proportion of participants with good sleep quality increased, while no participants remained in the poor sleep quality category after the intervention. The mean sleep quality score decreased from pre-test to post-test, indicating improved sleep quality, and the difference was statistically significant (p < 0.05). Conclusion: Benson relaxation therapy was effective in improving sleep quality among perimenopausal women. The intervention offers a simple, safe, and feasible non-pharmacological approach for managing sleep disturbances during the perimenopausal period.